Enhancing the photocatalytic activity of commercial P25 TiO2 powder by combining with handmade ni-doped TiO2 powder - Yoshiki Kurokawa; Dang Trang Nguyen; kozoK Taguchi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Titanium dioxide (TiO_2) is the most popular photocatalytic material. However, its operation is limited to UV light only. In this paper, we tried to improve the visible light responsiveness of TiO_2 by doping Nickel (Ni) using sol-gel method. By combining Ni-doped TiO_2 powder with commercially available P25 TiO_2 powder to make photocatalytic thin films, significant improvement in photocatalytic activity has been obtained. Furthermore, we also studied the relationship between the surface condition of photocatalytic thin films and their photocatalytic activity. The surface condition was improved by multilayer electrophoresis deposition method. Based on experimental results, by combining 10 - 20 wt% Ni-doped TiO_2 with P25 TiO_2, we could significantly enhance the photocatalytic activity of P25 TiO_2.